Regard sur les ensembles mobiliers civils bourguignons - Anne-Bénédicte Clert; Bruno François; Adeline Rivière; Michaël Vottero (In Situ)
The Burgundy region, like many others, can count a certain number of civil movable objects that enjoy protection as historic monuments. Town halls, theatres, administrative buildings, hospitals... can all be places where such historic objects are preserved. They can also contain ensembles of movable objects specifically commissioned and designed for furnishing and decoration purposes. Such collections are fragile. They are regularly studied and protected by the region’s curators of antiquities and art objects. Our collective text attempts an overview of some of the region’s more remarkable collections and offers a plural vision of this type of heritage and some of the problems it raises.